Nicomachus Theorem Sum of Cubic Numbers


$\textbf{Nicomachus}$ discovered “Nicomachus Theorem” interesting number patterns involving cubes and sums of odd numbers. Nicomachus was born in Roman Syria (now, Jerash, Jordan) around 100 AD. He wrote in Greek was a Pythagorean.

$\textbf{Nicomachus Theorem: Cubes and Sums of Odd numbers}$

\begin{eqnarray*}
1 &=& 1^3 \\
3 + 5 &=& 8 = 2^3 \\
7 + 9 + 11 &=& 27 = 3^3 \\
13 + 15 + 17 + 19 &=& 64 = 4^3 \\
21 + 23 + 25 + 27 + 29 &=& 125 = 5^3 \\
&\vdots&
\end{eqnarray*}

In general, $(n^2-n+1)+(n^2-n+3)+\cdots+(n^2-n+2n-1)=n^3$.

In particular, the first term for $(n+1)^3$ is $2$ greater than the last term for $n^3$.

  • $3$ is $2$ greater than $1$
  • $7$ is $2$ greater than $5$
  • $13$ is $2$ greater than $11$
  • $21$ is $2$ greater than $19$

The $n^{\text{th}}$ cubic number $n^3$ is a sum of $n$ consecutive odd numbers.

The identity is;
$$\sum_{k=1}^n \big[n(n-1)+2k-1\big] = n^3$$

$\textit{Proof}$

\( \begin{aligned} \displaystyle
\sum_{k=1}^n \big[n(n-1)+2k-1\big] &= \sum_{k=1}^n (n^2 – n + 2k -1) \\
&= \sum_{k=1}^n (n^2-n) + \sum_{k=1}^n {2k} – \sum_{k=1}^n {1} \\
&= n(n^2 – n) + 2(1+2+3+\cdots+n) – (1+1+1+\cdots+1) \\
&= n(n^2 – n) + 2 \times \dfrac{n}{2}(1+n) – n \\
&= n^3 – n^2 + n + n^2 – n\\
&= n^3
\end{aligned} \)

$\textbf{Nicomachus Theorem: How Squares and Cubes Meet}$

\begin{eqnarray*}
1^3 &=& 1^2 \\
1^3 + 2^3 &=& (1 + 2)^2 \\
1^3 + 2^3 + 3^3 &=& (1 + 2 + 3)^2 \\
1^3 + 2^3 + 3^3 + 4^3 &=& (1 + 2 + 3 + 4)^2 \\
\vdots \\
1^3 + 2^3 + 3^3 + \cdots + n^3 &=& (1 + 2 + 3 + \cdots + n)^2
\end{eqnarray*}

$\textit{Proof by Mathematical Induction}$

Step 1: Show it is true for $n=1$.
$\text{LHS} = 1^3 = 1 $
$\text{RHS} = 1^2 = 1$
$\therefore$ It is true for $n=1$.

Step 2: Assume it is true for $n=k$.
That is, $1^3 + 2^3 + \cdots + k^3 = (1+2+\cdots+k)^2$.

Step 3: Show it is true for $n=k+1$.
That is, $1^3 + 2^3 + \cdots + k^3 + (k+1)^3 = (1+2+\cdots+k+k+1)^2$.
\( \begin{aligned} \displaystyle
\text{LHS} &= 1^3 + 2^3 + \cdots + k^3 + (k+1)^3 \\
&= (1+2+\cdots+k)^2 + (k+1)^3 \\
&= \Big[\dfrac{k}{2}(1+k)\Big]^2 + (k+1)^3 \\
&= \dfrac{k^2}{4}(1+k)^2 + (k+1)^3 \\
&= (1+k)^2\Big[\dfrac{k^2}{4}+(k+1)\Big] \\
&= (1+k)^2 \times \dfrac{k^2+4k+4}{4} \\
&= \dfrac{(1+k)^2}{4}(k+2)^2 \\
&= \dfrac{(1+k)^2}{4}(1+k+1)^2 \\
&= \Big[\dfrac{1+k}{2}(1+k+1)\Big]^2 \\
&= (1+2+\cdots+k+k+1)^2 \\
&= \text{RHS}
\end{aligned} \)

$\textit{Proof by Geometry}$

The picture shows;

  • the area of the red square is $1=1^3$.
  • the area of the yellow square is $3^2-1=8=2^3$.
  • the area of the blue square is $6^2-3^2=27=3^3$.
  • the area of the green square is $10^2-6^2=647=4^3$.

So the total area is the sum of consecutive cubes, which is $1^3 + 2^3 + 3^3 + 4^3$.
Reading along the top edge we find $1+2+3+4$, the sum of consecutive numbers. But the area of a square is the square of the length of its side, which is $(1+2+3+4)^2$.

\( \begin{align}
1^3 + 2^3 + 3^3 + 4^3 &= (1+2+3+4)^2 \\
\therefore 1^3 + 2^3 + 3^3 + \cdots + n^3 &= (1+2+3+ \cdots + n)^2 \\
\end{align} \)

Algebra Algebraic Fractions Arc Binomial Expansion Capacity Chain Rule Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorials Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Proof Pythagoras Theorem Quadratic Quadratic Factorise Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Your email address will not be published.